2021
DOI: 10.3390/ma14092311
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Influence of Tool Electrode Material on Electrochemical Micromachining of 304 Stainless Steel

Abstract: Different cathode materials have different surface chemical components and machining capacities, which may finally result in different machining quality and machining efficiency of workpieces. In this paper, in order to investigate the influence of cathode materials on the electrochemical machining of thin-walled workpiece made of 304 stainless steel, five cylindrical electrodes are used as the target working cathodes of electrochemical machining to conduct experiments and research, including 45# steel, 304 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…19c). This indicates that materials such as stainless steel (~10 6 S/m) (Bian et al, 2021), graphite (~10 5 S/m) (Pradeep et al, 2019;Sugita et al, 2013a), carbon nanotubes (~10 4 S/m) (Meng et al, 2020), and heavily doped silicon (~10 4 S/m) Liu et al, 2018a) can also be used as tool materials theoretically. When the conductivity is 5×10 3 S/m, the current density is up to 150 A/cm 2 , which can be used as a tool material by increasing the voltage, but the heat are obtained by wet etching.…”
Section: Mechanical-electrochemical (Discharge) Energy Couplingmentioning
confidence: 99%
“…19c). This indicates that materials such as stainless steel (~10 6 S/m) (Bian et al, 2021), graphite (~10 5 S/m) (Pradeep et al, 2019;Sugita et al, 2013a), carbon nanotubes (~10 4 S/m) (Meng et al, 2020), and heavily doped silicon (~10 4 S/m) Liu et al, 2018a) can also be used as tool materials theoretically. When the conductivity is 5×10 3 S/m, the current density is up to 150 A/cm 2 , which can be used as a tool material by increasing the voltage, but the heat are obtained by wet etching.…”
Section: Mechanical-electrochemical (Discharge) Energy Couplingmentioning
confidence: 99%
“…Zhang et al confirmed that the utilization of an external rinse solution around the machining area effectively decreased the radius of the stray corrosion-affected area [23]. Bian et al investigated the effect of cathode materials on the electrolytic machining of stainless steel with tool tube electrodes and experimentally concluded that the use of 6061 aluminum alloy effectively mitigated the stray current corrosion during the machining process and reduced the hole taper [24]. Özerkan designed a device for processing small diameter holes in powder metal steel, which achieved a 65% reduction in electrolyte consumption by rotating the tool tube electrode while simultaneously enhancing the efficiency of debris discharge from the side machining gap [25].…”
Section: Introductionmentioning
confidence: 99%
“…Among these wave forms triangular wave forms improves the accuracy. Bian et al [6] attempted with five different electrodes namely SS, aluminium alloy, brass, tungsten and steel to realize the influence of tool materials on the EMM performance. The stray current effect in the machining zone was slowed down while using aluminium alloy due to the formation of oxide layers on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%